Study on Corporate Governance and Default Effect of Financial Lease Debt - Wang, Xiaoran (International Journal of Accounting and Financial Reporting, 2024)
This paper empirically analyzes the corporate governance effect and default of financial lease debt. The results show that: (1) Financial lease debt is conducive to reducing asset substitution, expanding debt scale, optimizing debt structure, reducing corporate debt cost, extending debt maturity and adjusting corporate investment, etc., and is conducive to solving corporate agency problems. (2) The corporate governance effects of financial lease debt with different transaction types and term structures are heterogeneous. In terms of transaction types, direct financial leasing can reduce agency costs, reduce inefficient investment, and have significant corporate governance effects. Sale-leaseback can alleviate the agency problem to some extent, but it can not restrain the inefficient investment. Other financial leases do not have corporate governance effects. In terms of term structure, short-term financial leasing has stronger corporate governance effect than long-term financial leasing. In addition, through the analysis of debt default distance (DTD), this paper finds that compared with direct financial leasing, the probability and default level of debt default are higher under the impact of COVID-19. When the company's future earnings decline or cash flow fluctuation range is 15%, the sale-leaseback debt has potential default risk.